Mortality trends in Acute Coronary Syndrome In Sahid Gangalal National Heart Centre - Rajbhandari, S; KC, MB; Sharma, D; Malla, R; Regmi, S; Limbu, Y.R.; Maskey, Arun; Rajbhandari, A; Bhatta, Y; Kansakar, S (Nepalese Heart Journal, 2004)
At the beginning of 20th century cardiovascular disease accounted for less than 10% of mortality worldwide. It has increased to 50% in the developed and 25% in the developing world at the end of the century. There has been steady decline in mortality due to acute myocardial infarction resulting from development of Coronary Care Unit, aspirin, beta blockade and Thrombolysis.